Anaerobic biodigester for sustainable biogas production on a rural property in the city of Açailândia, Maranhão, Brazil (Research, Society and Development, 2020)
This work had as objective, the construction and implantation of an economically viable biomass anaerobic digester for the sustainable production of biogas and natural biofertilizer, in a rural property in the municipality of Açailândia-MA. The biogas generation estimate was based on the percentage of volatile solids in the biomass (bovine manure) used. A daily generation of 300 kg of manure was obtained. The gravimetric methodology was used to calculate the percentage of total solids, volatile solids, and fixed solids. The organic load of the biodigester was calculated, the estimated flame time, light time, and reduced energy tariff. The system was assembled using low-cost materials. Methane production of 0.361 m³/day, making it possible to keep the flame of a domestic stove in operation for 49 min/day or used to generate approximately 2.33 kW/h per day or to keep a biogas lamp on for 5h and 27h min/day, and may also be saving R $ 1.30/day on the energy bill. In addition to gas, the process of methanization of cattle manure generated a natural biofertilizer, which can be commercialized or even used by the owner of the biodigester. Direct burning of the gas right after generation is beneficial, as it is complete combustion, generating only water and carbon dioxide, much less polluting than methane. The use of biodigesters and methanization are alternatives for replacing liquefied petroleum gas, which can possibly supply the demand for electrical or thermal energy and also reduce costs in communities and rural enterprises.